FCGR3A and FCGR2A Genotypes Differentially Impact Allograft Rejection and Patients' Survival After Lung Transplant - Paul, Pascale; Pedini, Pascal; Lyonnet, Luc; Di Cristofaro, Julie; Loundou, Anderson; Pelardy, Mathieu; Basire, Agnes; Dignat-George, Françoise; Chiaroni, Jacques; Thomas, Pascal; Reynaud-Gaubert, Martine; Picard, Christophe (Frontiers in Immunology, 2019)
Fc gamma receptors (FcγRs) play a major role in the regulation of humoral immune responses. Single-nucleotide polymorphisms (SNPs) of FCGR2A and FCGR3A can impact the expression level, IgG affinity and function of the CD32 and CD16 FcγRs in response to their engagement by the Fc fragment of IgG. The CD16 isoform encoded by FCGR3A [158V/V] controls the intensity of antibody-dependent cytotoxic alloimmune responses of natural killer cells (NK) and has been identified as a susceptibility marker predisposing patients to cardiac allograft vasculopathy after heart transplant. This study aimed to investigate whether FCGR2A and FCGR3A polymorphisms can also be associated with the clinical outcome of lung transplant recipients (LTRs). The SNPs of FCGR2A ([131R/H], rs1801274) and FCGR3A ([158V/F], rs396991) were identified in 158 LTx recipients (LTR) and 184 Controls (CTL). The corresponding distribution of genotypic and allelic combinations was analyzed for potential links with the development of circulating donor-specific anti-HLA alloantibodies (DSA) detected at months 1 and 3 after lung transplant (LTx), the occurrence of acute rejection (AR) and chronic lung allograft dysfunction (CLAD), and the overall survival of LTRs. The FCGR3A [158V/V] genotype was identified as an independent susceptibility factor associated with higher rates of AR during the first trimester after LTx (HR 4.8, p<0.0001, 95% CI 2.37-9.61), but it could not be associated with the level of CD16- mediated NK cell activation in response to the LTR’s DSA, whatever the MFI intensity and C1q binding profiles of the DSA evaluated. The FCGR2A [131R/R] genotype was associated with lower CLAD-free survival of LTRs, independently of the presence of DSA at 3 months (HR 1.8, p=0.024, 95% CI 1.08-3.03). Our data indicate that FCGR SNPs differentially affect the clinical outcome of LTRs and may be of use to stratify patients at higher risk of experiencing graft rejection. Furthermore, these data suggest that in the LTx setting, specific mechanisms of humoral alloreactivity, which cannot be solely explained by the complement and CD16-mediated pathogenic effects of DSA, may be involved in the development of acute and chronic lung allograft rejection.